2008
DOI: 10.1136/ard.2007.076174
|View full text |Cite
|
Sign up to set email alerts
|

Functional, molecular and proteomic characterisation of bone marrow mesenchymal stem cells in rheumatoid arthritis

Abstract: In spite of some restrictions related to the impaired clonogenic and proliferative potential, our findings support the use of autologous BM MSCs in RA and may have important implications for the ongoing efforts to repair tissue injury commonly seen in the course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 36 publications
4
126
1
4
Order By: Relevance
“…MSCs have the potential to differentiate into multiple cell types, including osteogenic, adipogenic, and chondrogenic cell lineages and may contribute to tissue repair and regeneration. In chronic inflammatory bone disease, bone formation and regeneration are inhibited, which may be related to the inflammatory microenvironment and may affect MSC differentiation [5,6]. Human periodontal ligament tissue-derived mesenchymal stem cells (PDLSCs) have been isolated as multipotent stem cells that are capable of being used in stem cell-mediated therapies and tissue engineering [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have the potential to differentiate into multiple cell types, including osteogenic, adipogenic, and chondrogenic cell lineages and may contribute to tissue repair and regeneration. In chronic inflammatory bone disease, bone formation and regeneration are inhibited, which may be related to the inflammatory microenvironment and may affect MSC differentiation [5,6]. Human periodontal ligament tissue-derived mesenchymal stem cells (PDLSCs) have been isolated as multipotent stem cells that are capable of being used in stem cell-mediated therapies and tissue engineering [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To further characterize patients' PBMC relative telomere length as appropriate or inappropriate for a given age, we defined the observed/predicted relative telomere length ratio (O/P ratio) for each patient according to the equation derived from the linear regression analysis of the correlation between the PBMC relative telomere values and age (years) of the controls (y = -158.18x + 13813). 24 We found that the mean O/P telomere length ratio of the patients (0.73±0.32) was out of the 95% confidence limits (CI) of the healthy controls (mean O/P telomere length ratio 1.01 ±0.56, 95% CI 0.87 and 1.14) suggesting inappropriate telomere loss according to age in CIN patients ( Figure 1C). Overall, the mean telomere length of patient PBMCs was significantly lower than that expected on the basis of the age-adjusted healthy control distribution (6203.26±1871.90; P=0.0004).…”
Section: Telomere Length Analysis Of Pbmcs In Cin Patients and Healthmentioning
confidence: 96%
“…Trypsinized MSCs from passage (P)-2 were induced to differentiate into adipocytes and osteoblasts as previously described [25,26]. Briefly, for the adipogenic differentiation, cells were cultured for 3 weeks in MSC medium supplemented with 10% FCS, 0.5 mM 1-methyl-3-butylisoxanthine, 1 mM dexamethasone, 0.2 mM indomethacin, and 10 mg/mL insulin.…”
Section: Msc Differentiation Assaysmentioning
confidence: 99%
“…MSC proliferative potential was evaluated by a Methyl Triazolyl Tetrazolium (MTT)-based assay in P2 cells and also by estimating the population doubling time through P2-P4 [26]. The formula 2 n = N x /N 0 was used for calculation of population doublings (n) at each passage based on the number of cells counted in the flask after trypsinization (N x ) and the number of cells initially plated (N 0 ).…”
Section: Proliferative Potential Of In Vitro Expanded Mscsmentioning
confidence: 99%
See 1 more Smart Citation